Combined analysis of three genome-wide association studies on vWF and FVIII plasma levels - Antoni, Guillemette; Oudot-Mellakh, Tiphaine; Dimitromanolakis, Apostolos; Germain, Marine; Cohen, William; Wells, Philip; Lathrop, Mark; Gagnon, France; Morange, Pierre-Emmanuel; Tregouet, David-Alexandre (Université d'Ottawa | University of Ottawa, 2011)
Abstract Background Elevated levels of factor VIII (FVIII) and von Willebrand Factor (vWF) are well-established risk factors for cardiovascular diseases, in particular venous thrombosis. Although high, the heritability of these traits is poorly explained by the genetic factors known so far. The aim of this work was to identify novel single nucleotide polymorphisms (SNPs) that could influence the variability of these traits. Methods Three independent genome-wide association studies for vWF plasma levels and FVIII activity were conducted and their results were combined into a meta-analysis totalling 1,624 subjects. Results No single nucleotide polymorphism (SNP) reached the study-wide significance level of 1.12 × 10-7 that corresponds to the Bonferroni correction for the number of tested SNPs. Nevertheless, the recently discovered association of STXBP5, STX2, TC2N and CLEC4M genes with vWF levels and that of SCARA5 and STAB2 genes with FVIII levels were confirmed in this meta-analysis. Besides, among the fifteen novel SNPs showing promising association at p < 10-5 with either vWF or FVIII levels in the meta-analysis, one located in ACCN1 gene also showed weak association (P = 0.0056) with venous thrombosis in a sample of 1,946 cases and 1,228 controls. Conclusions This study has generated new knowledge on genomic regions deserving further investigations in the search for genetic factors influencing vWF and FVIII plasma levels, some potentially implicated in VT, as well as providing some supporting evidence of previously identified genes.